Market Structure and Competition of Indonesian Eel in The Chinese Market - Sitty Nurzakiah; Rita Nurmalina; Netti Tinaprilla (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Indonesia is a major exporter of frozen eels to China. China consistently absorbed more than 80% of Indonesia's eel exports. Indonesian exports have been declining in recent years, whereas global demand, including China, is expected to grow. This may lead to competition among the exporting countries in the Chinese market.Purpose: This study aims to identify the structure of the frozen eel export market in China, the factors affecting the demand share, and to analyze the competition between Indonesia's frozen eel and other exporting countries in the Chinese market. Design/methodology/approach: The Herfindahl–Hirschman Index and Concentration Ratio (CR4 and CR8), and an Almost Ideal Demand System model. The data used were Secondary data from Indonesia, Malaysia, Thailand, Pakistan, and India from to 2012-2023. Findings/Results: The analysis shows that the export market structure of frozen eels in China is oligopolistic. Factors affecting the demand for Indonesia’s frozen eel in China are its own price, the price of frozen eel in the rest of the world, the exchange rate, and China’s GDP. Pakistan and Thailand have competed with Indonesia. Indonesian frozen eels are classified as normal goods, but are inelastic. Indonesia is the second-most benefited country in terms of China’s increase in import expenditure.Conclusion: Indonesia should leverage its competitive advantage in determining the pricing of frozen eels in the Chinese market and expand its market share in the global market. Furthermore, Indonesia can collaborate with Malaysia and India to capitalize on complementary market conditions. Originality/value (state of the art): This is the first study of its kind to examine the Indonesian Eel market structure and competitiveness in the Chinese market. It is also the first to integrate market structure theory with the AIDS model. Keywords: almost ideal demand system (AIDS) model, eels, export, Chinese market, international trade